CHARACTERIZATION OF k-CARRAGEENAN AND λ-CARRAGEENAN DERIVED FROM SEAWEED CHONDRACANTHUS CHAMISSOI AND ITS APPLICATION IN THE FOOD INDUSTRY - Salas de la Torre, Norma (2008)
The exploitation of algae producing carrageenan are intensified since the 80. Obtaining κ-carrageenan and λ-carrageenan is a function of the proper selection of algae, correct identification of the stages of life, control of parameters such as temperature, pH, time, concentration of solutions.The extraction process is based on: soluble in hot water and insolubility in polar organic solvents. Gametophyte phase is a starting point for the production of κ-carrageenan and phase sporophitic is geared to the production of λ - carrageenan. The ability gelling (κ-carrageenan) and performance viscosante (λ-carrageenan) of carrageenan are characteristics that apply to gelificar or thicken aqueous systems. The gelling fraction obtained was used in the formulation of dairy products. The κ-carrageenan obtained in the laboratory replaced Lactogel FL610 and Lactogel PS451 in the formulation of custard pudding and excellent consistency, texture, flavor, color and low calorie content.It can be used as a stabilizer in the processing of nectars replacing carboxymethylcellulose. Achocolatada milk produced with λ-carrageenan confirmed that carrageenan from the stage of life tetraspores imparts a higher viscosity suspensions.